New insights into the mechanisms controlling neutrophil survival - Cabrini, Mercedes (2010)
Purpose of review: Neutrophil survival is regulated by a complex convergence of different pathways. The present review analyzes these pathways and discusses how neutrophil survival is modulated during the course of inflammatory reactions. Recent findings: Although apoptosis appears to be the predominant cell death pathway in the neutrophil, recent data reveal that neutrophil survival is also regulated by a number of nonconventional pathways including NETosis, autophagic cell death, and other less characterized mechanisms. This supports an even more complex picture of the mechanisms involved in the regulation of neutrophil survival than previously thought. Summary: The control of neutrophil survival is central to homoeostasis and resolution of inflammation. Cell death is usually discussed dichotomously in terms of apoptosis or necrosis. There are two main pathways responsible for the stimulation of apoptosis; a death receptor pathway triggered by Fas, tumor necrosis factor α, and tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) and a mitochondrial pathway stimulated by a number of stressors such as DNA damage, growth factor deprivation, and chemotherapy drugs. Nonconventional pathways of neutrophil death include NETosis and autophagic cell death as well as a number of poorly characterized mechanisms. Understanding the integrated pathways responsible for the control of neutrophil survival holds therapeutic promise in infectious and inflammatory diseases.